Party Age and Party Color : New Results on the Political Economy of Redistribution and Inequality - Keefer, Philip; Milanovic, Branko (World Bank, Washington, DC, 2014)
This paper advances research on inequality with unique, new data on income distribution in 61 countries, including 20 Latin American countries, to explore the effects of political parties on redistribution. First, consistent with a central -- but still contested -- assumption of the political economy literature, left-wing governments redistribute more. In addition, consistent with recent research on the importance of party organization and the organizational differences between younger and older parties, older left-wing parties are more likely to internalize the long-run costs of redistribution and to be more credible in their commitment to redistribution, leading them to redistribute less. With entirely different data, the paper also provides evidence on mechanisms: left-wing governments not only redistribute more, they tax more; older left-wing parties, though, tax less than younger ones.